A Metacommunity Approach to Improve Biological Assessments in Highly Dynamic Freshwater Ecosystems. (22nd April 2020) - Cid, Núria; Bonada, Núria; Heino, Jani; Cañedo-Argüelles, Miguel; Crabot, Julie; Sarremejane, Romain; Soininen, Janne; Stubbington, Rachel; Datry, Thibault
Abstract: Rapid shifts in biotic communities due to environmental variability challenge the detection of anthropogenic impacts by current biomonitoring programs. Metacommunity ecology has the potential to inform such programs, because it combines dispersal processes with niche-based approaches and recognizes variability in community composition. Using intermittent rivers—prevalent and highly dynamic ecosystems that sometimes dry—we develop a conceptual model to illustrate how dispersal limitation and flow intermittence influence the performance of biological indices. We produce a methodological framework integrating physical- and organismal-based dispersal measurements into predictive modeling, to inform development of dynamic ecological quality assessments. Such metacommunity-based approaches could be extended to other ecosystems and are required to underpin our capacity to monitor and protect ecosystems threatened under future environmental changes.